Pengaruh Facilitating Conditions dan Behavioral Intention terhadap Use Behavior pada Pengguna Aplikasi BNI Mobile Banking - Ferghyna Ferghyna; Aditya Rachmadi; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
BNI mobile banking is a service/application that allows users to make banking transactions securely, easily, and quickly through a smartphone. The purpose Of This research is to know the interest in the user behavior of BNI mobile banking application based on unified theory of acceptance and use of technology (UTAUT) model. This research will analyze the influence of facilitating condition and behavioral intention variables on variable use behavior. Data collection is conducted by spreading questionnaire with 15 questions to 100 respondents and done online. The research data is processed with a descriptive approach and data calculation using SPSS version 25 program. The results of the study showed that the variables in the very high category were facilitating conditions of 84% and behavioral intention by 82%, while the use behavior variables were categorized as high as 64%. The results of the study also showed facilitating condition and behavioral intention variables to have a positive effect on the use behavior variables.